A Case Report and Literature Review of Bilateral Cervical Chondrocutaneous Branchial Remnants - Yuehua He; Huiling Zhu; Hang Ji; Weining Huang; Zhongrong Liu (Hindawi Limited, 2023)
Chondrocutaneous branchial remnants (CCBRs) are rare congenital heterotopic tissue formations originating from the first or second embryonic branchial arches. Clinically, CCBRs are characterized predominantly by unilateral and solitary cartilaginous nodules found on the lower neck region. Herein, we present a case of CCBRs in a 9-year-old male patient who presented with horn-shaped projecting masses on either side of the anterior border of the sternocleidomastoid muscle. The pathological report following surgical resection revealed that the lesion was located in the dermis and consisted primarily of hyaline cartilage tissue enclosed by a fibrous capsule, with few local vascular proliferations. Based on the clinical and pathological features, the patient was ultimately diagnosed with congenital bilateral cervical chondrocutaneous branchial remnants.